Analisis Pengaruh Kredit Mikro terhadap Kesejahteraan Masyarakat di Kecamatan Sumbawa : Studi Kasus Kelurahan Pekat dan kelurahan Brang Bara - Muhammad Iqbal; Rozzy Aprirachman (Jurnal Ekonomi dan Pembangunan Indonesia, 2026)
This study aims to examine the effect of microcredit on the level of community welfare in Kecamatan Sumbawa, with study locations in Kelurahan Pekat and Brang Bara. Microcredit is positioned as one of the strategic instruments in efforts to empower the economy of low-income communities, especially through increasing access to financing, income generation, and social welfare. This research uses a quantitative approach with Structural Equation Modeling (SEM) method based on Partial Least Square (PLS). The study population consisted of 100 micro-entrepreneurs in the two villages who had received microcredit from local financial institutions. The variables analyzed include ease of credit access (X1), credit repayment (X2), income (Y), and community welfare (Z) which acts as a mediating variable. The results of the analysis show that easy access to microcredit does not have a significant effect on income or community welfare. In contrast, the variable of microcredit repayment has a positive and significant effect on community welfare. In addition, income also has a positive and significant influence on welfare, indicating that an increase in income is a key factor in determining the economic and social welfare of microcredit recipient households. This finding confirms that the success of the microcredit program is more influenced by the effectiveness of the management and sustainability of the credit repayment system, rather than solely by the ease of access to financing.